Microfresamento do aço inoxidável 316L obtido por fusão seletiva a laser (SLM) utilizando ferramentas de metal duro com diferentes tipos de revestimentos - Silva, Letícia Cristina (2022)
Additive metal manufacturing (MAM) is a technology on the rise, considered promising for its ability to produce complex geometries, with fewer geometric restrictions. However, defects inherent to MAM directly influence the microstructure and mechanical properties of the printed part, in addition to the need for subtractive post-processing techniques, when dimensional, geometric and surface finish tolerances are required. In this context, this work aims to investigate the machinability of stainless steel ABNT 316L obtained by the selective laser melting (SLM) process by comparing the performance of micromills without coating and with coatings: AlCrN, DLC, TiN and TiAlN. To this end, tests were performed that consisted of machining microchannels, in two different types of printed samples using two different laser scanning techniques. From the experimental data, the evolution of wear, the shapes and mechanisms of tool wear, the roughness (Ra, Rq, Rz, Rt, Rsk, Rku), the micromachined surface, quantitative and qualitative aspects of burr formation were analyzed. and chips. The results show that the highest wear was obtained with the uncoated and DLC coated tools. The application of cutting fluid did not promote significant improvement in the reduction of wear. Rounding of the nose radius and flank wear are the predominant forms of wear in microtools, caused mainly by the adhesion and drag mechanism. The lowest roughness was obtained with the use of uncoated tools and in general favored by the structure of the sample called Block S and the use of MQL. The resulting machined surfaces were classified into five different types, in addition to the observation of pores and internal cavities located at the ends of the channels. The volume of burrs obtained is smaller than that observed in the machining of conventional metals and predominantly greater on the up-milling side, being aggravated when machined dry. Continuous type chips were identified, with ribbon or helical shapes and a high degree of chip settlement. Finally, the best performances were obtained by tools with TiAlN and AlCrN coatings, when the S-block was machined, and by the uncoated tools, when the C-block was machined. The best overall performance was obtained by the microtool with TiAlN coating when machining the S-block, without using cutting fluid.